The Genotype (A to H) Dependent N-terminal Sequence of HBV Large Surface Protein Affects Viral Replication, Secretion and Infectivity - Ou, Guomin; He, Lingyuan; Wang, Luwei; Song, Ji; Lai, Xinyuan; Tian, Xing; Wang, Lei; Zhang, Kai; Zhang, Xuechao; Deng, Juan; Zhuang, Hui; Xiang, Kuanhui; et al. (Frontiers in Microbiology, 2021)
Genetic variability has significant impacts on biological characteristics and pathogenicity of hepatitis B virus (HBV), in which the N-terminal sequence of the presurface 1 (preS1) region of HBV large surface protein (LHBs) displays genotype (GT) dependent genetic heterogeneity. As an important sequence element for binding to hepatocyte receptor (sodium taurocholate cotransporting polypeptide, NTCP), the biological roles of this very N-terminal sequence from different HBV genotypes are largely unknown. By analyzing 6563 full-length genome sequences of GTA-GTH extracted from HBVdb database, the preS1 N-terminal sequences were divided into four representative types, namely C-type (GTA, GTB and GTC), H-type (GTF and GTH), E-type (GTE and GTG) and D-type (GTD). Their roles on HBV replication in HepG2 and HepG2-NTCP cells were studied using GTC- and GTD-based plasmids harboring 1.3-mer HBV genomes or viral strains, in which the preS1 N-termini were substituted by sequence from each of the four representative types, respectively. We found that the C- and H-type LHBs preferred to attenuate HBV surface protein (HBs) secretion, while D- and E-type LHBs promoted infectivity. The different capacities of HBs secretion might be attributed to the amount of intracellular LHBs. The luciferase reporter assay of surface promoter I showed that transcription of LHBs mRNA could be increased by all tested preS1 N-termini modified types of LHBs. However, HBV core promoter activity was found to be differentially regulated with significant down-regulation of precore mRNA transcription by all mutants’ LHBs and up-regulation of pregenomic RNA only by E-type LHBs. Moreover, the levels of replicative HBV DNAs were increased by D-, H- and E-types, suggesting HBV DNA polymerase (Pol) activity might be modified by sequence variations in the Pol-spacer domain that overlaps with preS1 N-terminus. Taken together, the findings of the multiple roles of the genotype dependent heterogenous preS1 N-terminus on viral replication, secretion and infectivity advance our understanding of HBV biology. The novel finding also suggests that it is worth paying more attention to study the HBV strains with naturally occurring intergenotypic recombination at preS1 sequences.